(untitled) (Baghdad Science Journal, 2009)
Celiac disease is an autoimmune disorder induced by gluten intake in genetically susceptible individuals. The incidence of celiac disease in various autoimmune disorders is increased 10-30 fold in comparison to the general population and the prevalence of celiac disease was noted to be 2-5% in autoimmune thyroid disease. To detect the autoimmune thyroid disease in patients with celiac disease, we investigated 22 patients suspected with celiac disease of age 1-13 years old and 20 healthy controls. IgA and IgG antigliadin antibodies were measured in serum with celiac disease sample. The patients which were positive to gliadin antibody were carried out to T3, T4 and TSH by ELISA tests. There was no significant differences (P>0.05) in age group and gender of patients afflicted with celiac disease and there was highly significant deferances (P<0.01) with increased mean level of IgG antibody in sera of hyperthyroidism patients afflicted with celiac disease than normal group. We found a relationship between celiac disease and hyperthyroidism in patients. The aim of this study was to detect the autoimmune thyroid disease in patients with celiac disease.